2022
DOI: 10.21203/rs.3.rs-1617784/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial ecology of jaguars in Mexico: implications for conservation

Abstract: ContextMovement ecology contributes valuable information about animal interactions with the environment, and their responses to landscape-level anthropogenic impacts. Big cats are vulnerable to such changes, but the current deficit of information about home range movements, limits the scope of conservation initiatives. Objectives Describe the home range size, interactions, and differences between jaguar populations across its distribution in MexicoMethodsWe used 41,008 GPS-generated data points obtained from 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Our study revealed important information about jaguar ecology and behavior that will help in their management and conservation strategies and programs in the Yucatan Peninsula and southern Mexico, generally. The current population of about 2,000 jaguars in the Yucatan Peninsula in Mexico is the largest in a region that extends into Central America (Ceballos et al, 2016;Ceballos et al, in press), and conservation efforts there are pivotal to ensuring the stability of their population and the ecological services they provide.…”
Section: Implications For Conservationmentioning
confidence: 99%
See 3 more Smart Citations
“…Our study revealed important information about jaguar ecology and behavior that will help in their management and conservation strategies and programs in the Yucatan Peninsula and southern Mexico, generally. The current population of about 2,000 jaguars in the Yucatan Peninsula in Mexico is the largest in a region that extends into Central America (Ceballos et al, 2016;Ceballos et al, in press), and conservation efforts there are pivotal to ensuring the stability of their population and the ecological services they provide.…”
Section: Implications For Conservationmentioning
confidence: 99%
“…Landscape-level conservation strategies are needed to conserve jaguar populations. However, currently protected natural areas in the Yucatan Peninsula are discontinuous, and while most regions are still connected with corridors of forests and other natural ecosystems, these areas often lack official protection against deforestation (Ceballos et al, 2016;Ceballos et al, 2018). Together with other research, our study suggests that a major effort must be initiated to expand the size of the protected areas such as the Calakmul Biosphere Reserve, create additional protected areas, and design and protect biological corridors (see also Ceballos et al, 2016Ceballos et al, , 2018.…”
Section: Implications For Conservationmentioning
confidence: 99%
See 2 more Smart Citations